Exploring the Malaysian English Newspaper Corpus for Lexicographic Evidence - Tan Siew Imm (Kajian Malaysia, 2014)
This paper describes the analysis of the Malaysian English Newspaper Corpus for lexicographic evidence, and demonstrates the use of corpus data and information obtained from secondary sources in creating dictionary entries for 457 Malaysian English loanwords, compound blends, loan translations and lexical creations. Consisting primarily of nouns, these features include food names, terms for festivals and religious practices, names of social and recreational activities, and honorific titles and terms of respect. These features are produced and understood by the community, and are generally considered acceptable for use across a wide range of intranational domains. The dictionary entries created through the project described in this article will require revisions as more corpora, representing diverse registers of Malaysian English, become available. New lexical features will also need to be codified. The influences of languages other than Malay and Chinese should also be examined. Although core English words should be central to a Malaysian English dictionary, how some of these words have been adapted in the local sociolinguistic context will also have to be explored. These dictionary entries should be relevant to the educational and communicational needs of the society while maintaining an endonormative standard. It is argued that the codification of the vocabulary of Malaysian English can be an effective way to signal the legitimacy and the coming of age of this variety.